De volta ao mundão: um estudo sobre o retorno do jovem egresso da medida socioeducativa de internação ao convívio social - Marcela Silva Andrade (2012)
This study aimed to analyze how is the return to social life of the young egress of the social-educative detention procedure, as well as the impact of this procedure in their daily lives. The subjects of this study were students who had reached the age of criminal responsability and did not have more legal issues. We used as instruments in-depth interviews with two young egress, interviews with professionals and analysis of reports and treatments filed in the technical center of Vara Infracional da Infância e Juventude of Belo Horizonte. We use the ergological perspective, which considers the theoretical and the practical experience of life knowledge both at the same importance level, to approach the reality studied. Our premise is that we live in a punitive society, which blames the individuals for their actions through punishment. We bounded the place of justice, especially the criminal justice system, considering that this system is flawed when it comes to fulfill his goal of "re-socialize", and aims to neutralize part of the population that is considered "dangerous", for that population are out of the consumer society. We use the Critical Criminology and Criminal Abolitionism theoretical to understand this phenomenon. Analyzing the current laws on the childcare system and the rights relating to young people, we find that there is a disagreement between what is prescribed and what actually happens in the exercise of these rights. It is possible to affirm that the social-educative procedure is punishment to the young and cannot be understood as a "good" offered to him. On return to social life, young people face challenges in accessing specialized health and school, even with the egress program assistance. The social vulnerability is not altered, and may be aggravated by deprivation of freedom, especially on the stigma that the young takes. Inequalities of class are present in the exercise of basic rights. On returning to the community, marked by meeting the police and by the subjective need to find their identity as a man, these kids become eternal guilty, returning to the system of punitive control. Even if the deprivation of freedom brings some positive effects for a few young people, the damages that come along do not justify these potential goods that can be enjoyed in freedom. Depriving young people of their freedom in the name of "rehabilitation" does not seem possible. Psychological explanations that individualize the phenomenon of so-called "criminality" does not seem to be contributing to social transformation either. Thus, the arrest and genocide of the poor youth need to be understood in a socio-historical perspective. Given the failure of the punitive system and class inequality, it is necessary to find new ways to solve our social conflicts.